The role of nanoparticles in the inhibition of multidrug-resistant bacteria and biofilms - Al Matar, Manaf; Makky, Essam A.; Isil, Var; Koksal, Fatih (Bentham Science Publishers B.V., 2018)
Until recently, one of the main reasons for mortality has been infectious diseases, and bacteria that are drug-resistant have emerged as a result of the wide application, as well as the misuse of antibacterial medications. Having multidrug-resistance, bacteria present a great problem for the efficient management of bacterial infections and this challenge has resulted in the creation of other means of dealing with bacterial diseases. Of late, metallic nanoparticles (NPs), employed as antibacterial agents, have the potential for use against resistance to bacterial drugs.